2019
DOI: 10.1002/jia2.25397
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cumulative viraemia following treatment initiation with different antiretroviral regimens: a real‐life study in Brazil

Abstract: Introduction The relative efficacy of different antiretroviral (ART) regimens has been extensively evaluated in the context of clinical trials, using HIV viral load (VL) measurements at pre‐specified timepoints after ART onset. However, data from real‐life studies using combined longitudinal measurements of cumulative viraemia are scarce. This study aimed to address the independent effect of different ART regimens on HIV cumulative viraemia over the first 12 months after treatment initiation, using programmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Our findings are consistent with previous studies that have assessed and demonstrated the efficacy of dolutegravir-based regimen in the treatment of PLWH [15][16][17]. A large retrospective cohort study in Brazil using program level data also shows viral suppression by 12 months was 84.0 percent with TLE and 90.5% with TLD.…”
Section: Resultssupporting
confidence: 92%
“…Our findings are consistent with previous studies that have assessed and demonstrated the efficacy of dolutegravir-based regimen in the treatment of PLWH [15][16][17]. A large retrospective cohort study in Brazil using program level data also shows viral suppression by 12 months was 84.0 percent with TLE and 90.5% with TLD.…”
Section: Resultssupporting
confidence: 92%
“…Some studies reported that INSTI-based regimens are associated with lower RV than other regimens. Pascom et al performed a very large study that compared cumulative viremia during the first 12 months of ART in 112,243 individuals [155]. INSTI-based regimens were associated with significantly lower cumulative RV compared to both PI-based and NNRTI-based regimens.…”
Section: Differences In Residual Viremia and Other Hiv Reservoir Markmentioning
confidence: 99%
“…ART is available exclusively through the public health system to registered persons. Data concerning CD4+ T cell counts and HIV viral load are available for persons undertaking laboratory testing in the public health system, comprising $84% of all PLHIV who are registered in care [19].…”
Section: Methodsmentioning
confidence: 99%
“…The database includes information from all PLHIV in Brazil who are registered in care; this corresponds roughly to the totality of diagnosed PLHIV, since ART is available exclusively through the public health system to registered persons. Data concerning CD4+ T cell counts and HIV viral load are available for persons undertaking laboratory testing in the public health system, comprising ~84% of all PLHIV who are registered in care [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation